Palateless custom bar supported overdenture: A treatment modality to treat patient with severe gag reflex - Kunwarjeet Singh; Nidhi Gupta (Wolters Kluwer Medknow Publications, 2012)
Objective: To suggest a custom bar supported overdenture treatment modality for prosthodontic management of patients with severe gag reflex. Background: Some patients have a severe gag reflex and cannot tolerate conventional maxillary complete dentures with maximum palatal coverage and extensions of all borders. The condition further gets complicated in patients suffering from respiratory problems along with severe gag reflex. Severe gagging acts as a barrier to treat such patients with accepted clinical procedures and prevent patients from wearing the prosthesis. By saving some of the remaining natural teeth and fabricating, a horse shoe shape palateless simple tooth or bar supported overdenture can be successfully used for treating such patients. Materials and Methods: The remaining maxillary right and left canines were prepared with the tapered round end diamond bur to receive copings of custom bar after intentional root canal treatment of same teeth. Impression was made with light body and putty of the polyvinyl siloxane elastomer with double step putty wash technique. Impression was poured with die stone. Wax pattern of copings with bar was fabricated with inlay wax which was invested and casted. After retrieving the bar, it was finished and its fit was evaluated. The coping-bar assembly was finally cemented with the glass ionomer cement. Palateless overdenture was fabricated by conventional technique used for the fabrication of complete denture. Conclusion: Palateless custom bar supported overdenture procedure can be successfully used for the management of patients with severe gag reflex with improved denture retention, stability, chewing efficiency and comfort of the patient.